2022
DOI: 10.1186/s43141-021-00285-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and molecular implications of ecofriendly made silver nanoparticles treatments in pea (Pisum sativum L.)

Abstract: Background Silver nanoparticles (AgNPs) are the most widely used nanomaterial in agricultural and environmental applications. In this study, the impact of AgNPs solutions at 20 mg/L, 40 mg/L, 80 mg/L, and 160 mg/L on cell ultrastructure have been examined in pea (Pisum sativum L) using a transmission electron microscope (TEM). The effect of AgNPs treatments on the α, β esterase (EST), and peroxidase (POX) enzymes expression as well as gain or loss of inter-simple sequence repeats (ISSRs) marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…These results may indicate that as the concentration of biologically synthesized Ag NPs increases, toxic effects are spread from septic cap cells to epidermal and cortical cells of the root apex and elongation zone. The genotoxic effects of Ag NPs, including aberrations in mitosis, nuclear erosion and elongation, and chromosome damage, have been previously documented in wheat [ 31 ], faba bean [ 47 ], and garden pea [ 48 ] seedlings. In our study, increased fluorescence in root tips under (Bio)Ag NPs ( Figure 4 ) indicating ROS generation interacted with increased numbers of dead cells ( Figure 5 C,D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may indicate that as the concentration of biologically synthesized Ag NPs increases, toxic effects are spread from septic cap cells to epidermal and cortical cells of the root apex and elongation zone. The genotoxic effects of Ag NPs, including aberrations in mitosis, nuclear erosion and elongation, and chromosome damage, have been previously documented in wheat [ 31 ], faba bean [ 47 ], and garden pea [ 48 ] seedlings. In our study, increased fluorescence in root tips under (Bio)Ag NPs ( Figure 4 ) indicating ROS generation interacted with increased numbers of dead cells ( Figure 5 C,D).…”
Section: Resultsmentioning
confidence: 99%
“…However, our observations did not confirm this, because coleoptile growth was inhibited to the same extent by (Bio)Ag NPs at concentrations of 10 as 40 mg/L ( Figure 3 ). Therefore, other factors such as changes in transpiration/metabolism of phytohormones and increased ROS production [ 45 , 46 , 48 , 49 , 50 ] presumably contribute to this.…”
Section: Resultsmentioning
confidence: 99%
“…It is also a model object of legumes for genetic studies [ 40 ]. There are only a few reports describing the effect of Ag NPs on germination [ 26 , 41 ], root development [ 26 ], as well as on ultrastructural and molecular changes in the leaves and roots of pea seedlings [ 42 ]. These studies showed that Ag NPs at low concentration (20 mg/L) did not affect pea germination, whereas at higher levels (80–160 mg/L) they inhibited both germination and seedling growth and caused distinct root deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a decreasing number of chloroplasts with deformed shapes was observed in cotyledons of Ag NPs-treated seedlings. A molecular study showed an increase in the activity of some enzymes (α, β esterase and peroxidase) and genotoxic effects of Ag NPs on the genome manifested by DNA damage [ 42 ]. Thus, it can be expected that Ag + ions originating from Ag NPs can also affect cell metabolism [ 3 ], but evidence for this in pea plants is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Its seeds are rich in proteins, fibers, vitamins, minerals, and antioxidants [ 2 ]. In addition, the pea is widely used as a model plant species nowadays [ 3 , 4 ], and also is a historically important genetic model as the first organism for which the basic genetics laws were described and demonstrated by the Moravian monk Gregor Johann Mendel in 1865 [ 5 , 6 ]. His systematic work, statistic evaluation, and mathematical descriptions of his experiments with hereditary of seven independent pea features paved the foundation of modern genetics.…”
Section: Introductionmentioning
confidence: 99%